Iowa RBA, August 12, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for August 12, 1996. Highlights of the update include sightings of Red-necked Phalaropes, Snowy Egrets, and Little Blue Herons. Also included are handwritten notes for the next week's update with sightings of a Red-breasted Nuthatch, Ruddy Shelduck, and a Ringed Turtle-Dove. Epson - sheet feed/flatbed